Collaborative Governance Performance in Grant Policy to Foreign Governments/Foreign Institutions - Rizal Sukma Pradika; Retno Kusumastuti (International Journal of Economics Development Research (IJEDR), 2023)
Governance reform in granting to foreign governments/foreign institutions was marked by the issuance of Government Regulation 48 of 2018 concerning Procedures of Grants to Foreign Governments/Foreign Institutions. This new grant regulation aims to centralize grant budget allocations to Indonesian AID. The business process of grants to foreign governments/foreign institutions involves the Ministry of Foreign Affairs as the actor that determines policy directions and targets, the Ministry of Finance as the actor who negotiates and signs the grant agreement, Indonesian AID as the executor of the grant, and technical ministries/agencies as units—proposing grants, as well as state-owned enterprises and domestic business actors participating in the supply of goods/services for grant commodities. The role of each of these organizations shows the existence of collaborative governance in the policy of grants to foreign governments/foreign institutions. In its implementation, the realization of grants still needs to reach the target set. It is an indication of difficulties in the process of collaborative governance. For this reason, this study aims to assess the performance of collaborative governance by using the Collaborative Governance Regime (CGR) performance dimension matrix. The results of this study found obstacles, including 1) the List of Planning Grants (DRPH) that were late, which had an impact on the realization of grants, and 2) the outcomes of the policy of grants to foreign governments/foreign institutions do not yet have clear indicators, so they are still not measurable. For this reason, the suggestion from this research is that it is necessary to formulate an outcome measure of the policy of grants to foreign governments/foreign institutions so that it can be used as a monitoring and evaluation tool, not only for the outcomes themselves but also for the collaborative governance process within them.